2012
DOI: 10.1016/j.jprot.2012.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of serum proteomic biomarkers for prediction of response to infliximab (a monoclonal anti-TNF antibody) treatment in rheumatoid arthritis: An exploratory analysis

Abstract: Biologics such as TNF antagonists are a new class of drugs that have greatly improved Rheumatoid Arthritis (RA) treatment. However, for unknown reasons, individual patients with RA respond to one of these drugs but not to others even those targeting the same molecule. Methods to predict response are sorely needed because these drugs are currently selected by trial and error, what is very inefficient and prejudicial for the patient and the healthcare system. Here, we have explored the discovery of protein bioma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
37
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 78 publications
(80 reference statements)
1
37
0
Order By: Relevance
“…Genetic markers also offer promise with a recent large genome-wide association study reporting the first definitive genetic association (in the CD84 gene) with anti-TNF response [25]. Other smaller studies suggest that stimulated whole blood cell pro-inflammatory cytokine levels [26] and serum proteins [27] may be useful in predicting anti-TNF efficacy. These findings are promising but lack clinical utility, since most markers require validation in larger cohorts or associate with only small differences in treatment response.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic markers also offer promise with a recent large genome-wide association study reporting the first definitive genetic association (in the CD84 gene) with anti-TNF response [25]. Other smaller studies suggest that stimulated whole blood cell pro-inflammatory cytokine levels [26] and serum proteins [27] may be useful in predicting anti-TNF efficacy. These findings are promising but lack clinical utility, since most markers require validation in larger cohorts or associate with only small differences in treatment response.…”
Section: Discussionmentioning
confidence: 99%
“…The other six studies all proposed predictors of response to therapy; however, none of these studies performed a technical replication or separate validation in new patients, and the overlap of discovered predictors between studies is restricted to CCL2 (monocyte chemoattractant protein-1, MCP-1), which has been cross-validated in two studies (14,15). However, CCL2 was not shown to be predictive in our study and was not identified in the studies using mass spectrometry (17,18), implying that it is not a consistent predictor. Several other proteins proposed as predictors in earlier studies were measured in our xMAP panel, including chemokine (C-X-C motif) ligand 4 (CXCL4), granulocyte-macrophage colony-stimulating factor (GM-CSF), IL-1α, IL-1β, IL-6, IL-8, IL-15, IL-19, IP-10, and TNF-α.…”
Section: Discussionmentioning
confidence: 68%
“…It is therefore not expected that patients with a low DAS28 and high HAQ will have a better response to any non-TNFi. Proteomic approaches to the prediction of response have been studied before (14)(15)(16)(17)(18)(19)(20)(21)). An overview of these studies and reported results is presented in Table 5.…”
Section: Discussionmentioning
confidence: 99%
“…We have provided a dynamic list of proteins which were significantly altered in the circulation of LAM patients, three of which we validated in individual LAM and healthy control samples in order to strengthen the mass spectrometry findings. The strength of this study is that we have validated, in a larger population, four of the proteins (similar to other serum screening studies [39]) identified to differ in two separate LAM cohorts subsequent to screening with iTRAQ labels.…”
Section: Discussionmentioning
confidence: 77%